ETBR gel filter; Go green in DNA analysis - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Mohammad Ahmed, Isa; Omar Alshajrawi, Mohd; Muhammad Umer, Khan; Mohammad Alglebat, Mahmod (2018)
Ethidium bromide (chemical names:Dromilac, Homidium bromide or 3,8-Diamlno-5-ethyl-6-phenylphenanthridlnium bromide) fluoresces, when exposed to ultra violet light. Therefore, it is commonly used in analytical laboratories for visualizing nucleic acids. Ethidium bromide exhibits a vivid red-orange color when bound to nucleic acids. Elhidium bromide can be absorbed through exposed skin and mucus membranes. According to the PubChem-Laboratory Chemical Safety Summary (LCSS), Ethidium bromide is classified as an irritant to the eyes and skin, harmful if swallowed, toxic if inhaled and it is suspected to cause gen etic defects besides its carcinogenic effects. We have developed a novel, simple and cost-effective equipment to discard ethidium bromide In a short time by easiest and safest way. We designed a special filter made of activated charcoal with other inactive ingredients (under copyright). Because adsorption works by chemically binding the impurities to the carbon, the active sites in the charcoal eventually become filled. Activated charcoal filter becomes less effective with use and have to be replaced. The device consists of 3 main parts: the upper part is a stainless-steel basin containing electrical heating rods to melt gels containing ethidium bromide in the boiling water, the middle part is a disposable filter containing 5 layers, and the lower part is a rein forced Ober tank to collect the final liquid w1W disposed off in the sink (either directly or until fill it). The device has a keyboard to control the temperature, lime and changing the filler to incorporate towards IR 4.0 requirement as per ease of the use.